2019
DOI: 10.1186/s12991-019-0248-0
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality in patients with treatment-resistant depression: a cohort study in the US population

Abstract: Background Treatment-resistant depression (TRD) may represent a substantial proportion of major depressive disorder (MDD); however, the risk of mortality in TRD is still incompletely assessed. Methods Data were obtained from Optum Clinformatics™ Extended, a US claims database. Date of the first antidepressant (AD) dispensing was designated as the index date for study entry and 6 months prior to that was considered the baseline period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
2
46
0
1
Order By: Relevance
“…To our knowledge, only two previous studies, one from Sweden and one from the US, have compared the all-cause mortality in patients with TRD versus non-TRD MDD [ 13 , 28 ]. Both studies reported 29–35% higher overall mortality in patients with TRD compared with non-TRD patients [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only two previous studies, one from Sweden and one from the US, have compared the all-cause mortality in patients with TRD versus non-TRD MDD [ 13 , 28 ]. Both studies reported 29–35% higher overall mortality in patients with TRD compared with non-TRD patients [ 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two previous studies, one from Sweden and one from the US, have compared the all-cause mortality in patients with TRD versus non-TRD MDD [ 13 , 28 ]. Both studies reported 29–35% higher overall mortality in patients with TRD compared with non-TRD patients [ 13 , 28 ]. Our study demonstrated a 38% increase in mortality in the TRD group compared with the non-TRD group in an age- and gender-adjusted model (HR: 1.38; 95% CI: 1.21–1.57), which is similar to the increases in mortality reported in the two aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious mental illnesses are not alone in affecting CVD mortality. Depression is also significantly associated with excess mortality [14], with treatmentresistant depression, in particular, resulting in higher allcause [15] and cardiovascular [16] mortality, compared to non-treatment-resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…Failure of a treatment course was defined as a switch of an AD (no more than 180 days after the end of the previous treatment), the addition of an AD, or the initiation of an augmentation therapy. Initiation of a third AD or augmentation medication defined TRD, consistent with recent literature using insurance claims databases to identify patients with TRD 10,[16][17][18][19][20][21][22] .…”
Section: Study Design Sample Selection and Study Cohortsmentioning
confidence: 64%